Cocktail effects in understanding the stability and properties of face-centered-cubic high-entropy alloys at ambient and cryogenic temperatures. (October 2020) - Cao, B.X.; Wang, C.; Yang, T.; Liu, C.T.
Abstract: The multimetallic cocktails provide vast compositional space with unlimited elemental combinations and structural possibilities for alloy design. The crystallographic metastability and thermodynamic instability offer opportunities for the activation of athermal transformations and intermetallic phase formation, particularly when exposed to mechanical perturbations and thermal input. Elemental interactions between the constituent and/or interstitial elements attribute to the remarkable interstitial strengthening effect. The associated strengthening mechanisms and strain-hardening mechanisms are also discussed. Here, we attribute the above-mentioned properties to cocktail effects, which is originated from the synergistic multicomponent alloying. These results provide the insights for the development of structural materials via cocktail effects. Graphical abstract: Image, graphical abstract